Sound Clash - Cooper, C. author. aut Link
X, 348 p. 12 illus.
Keywords: Megawattage sound systems have blasted the electronically-enhanced riddims and tongue-twisting lyrics of Jamaica's dancehall DJs across the globe. This high-energy raggamuffin music is often dismissed by old-school roots reggae fans as a raucous degeneration of classic Jamaican popular music. In this provocative study of dancehall culture, Cooper offers a sympathetic account of the philosophy of a wide range of dancehall DJs: Shabba Ranks, Lady Saw, Ninjaman, Capleton, Buju Banton, Anthony B and Apache Indian. Cooper also demonstrates the ways in which the language of dancehall culture, often devalued as mere 'noise,' articulates a complex understanding of the border clashes which characterize Jamaican society, and analyzes the sound clashes that erupt in the movement of Jamaican dancehall culture across national borders.